"My math and me": Nursing students' previous experiences in learning mathematics. Issue 1 (January 2016) - Røykenes, Kari
Abstract: In this paper, 11 narratives about former experiences in learning of mathematics written by nursing students are thematically analyzed. Most students had a positive relationship with the subject in primary school, when they found mathematics fun and were able to master the subject. For some, a change occurred in the transition to lower secondary school. The reasons for this change was found in the subject (increased difficulty), the teachers (movement of teachers, numerous substitute teachers), the class environment and size (many pupils, noise), and the student him- or herself (silent and anonymous pupil). This change was also found in the transition from lower to higher secondary school. By contrast, some students had experienced changes that were positive, and their mathematics teacher was a significant factor in this positive change. The paper emphasizes the importance of previous experiences in learning mathematics to nursing students when learning about drug calculation. Highlights: Nursing students' with high math test anxiety and low math self-concept. Most students had a positive relationship with the subject in primary school. Change occurred in the transition to lower or upper secondary school. The subject, teachers, class environment were found as reasons for changes.